Evidence of an Epigenetic Modification in Cell-cycle Arrest Caused by the Use of Ultra-highly-diluted Gonolobus Condurango Extract - Bishayee Kausik; Sikdar Sourav; Khuda-Bukhsh Anisur Rahman (Journal of Pharmacopuncture, 2013)
Objectives: Whether the ultra-highly-diluted remedies used in homeopathy can effectively bring about modulations of gene expressions through acetylation/deacetylation of histones has not been explored. Therefore, in this study, we pointedly checked if the homeopathically-diluted anti-cancer remedy Condurango 30C (ethanolic extract of Gonolobus condurango diluted 10-60 times) was capable of arresting the cell cycles in cervical cancer cells HeLa by triggering an epigenetic modification through modulation of the activity of the key enzyme histone deacetylase 2 vis-a-vis the succussed alcohol (placebo) control. Methods: We checked the activity of different signal proteins (like p21WAF, p53, Akt, STAT3) related to deacetylation, cell growth and differentiation by western blotting and analyzed cell-cycle arrest, if any, by fluorescence activated cell sorting. After viability assays had been performed with Condurango 30C and with a placebo, the activities of histone de-acetylase (HDAC) enzymes 1 and 2 were measured colorimetrically. Results: While Condurango 30C induced cytotoxicity in HeLa cells in vitro and reduced HDAC2 activity quite strikingly, it apparently did not alter the HDAC1 enzyme; the placebo had no or negligible cytotoxicity against HeLa cells and could not alter either the HDAC 1 or 2 activity. Data on p21WAF, p53, Akt, and STAT3 activities and a cell-cycle analysis revealed a reduction in DNA synthesis and G1-phase cell-cycle arrest when Condurango 30C was used at a 2% dose. Conclusion: Condurango 30C appeared to trigger key epigenetic events of gene modulation in effectively combating cancer cells, which the placebo was unable to do.